Risk of mature B‐cell neoplasms and precursor conditions after joint replacement: A report from the Haematological Malignancy Research Network. Issue 3 (23rd November 2019) - Kane, Eleanor; Painter, Daniel; Smith, Alexandra; Lamb, Maxine; Oliver, Steven E.; Patmore, Russell; Roman, Eve
Abstract : Associations between previous joint replacement and B‐cell lymphoid malignancies have been reported, but despite numerous reports, associations with the disease subtypes have received little attention. Using a UK‐based register of haematological malignancies and a matched general population‐based cohort, joint replacements from linked hospital inpatient records were examined. Cases diagnosed 2009–2015 who were aged 50 years or more were included; 8, 013 mature B‐cell neoplasms comprising myeloma ( n = 1, 763), diffuse large B‐cell lymphoma (DLBCL, n = 1, 676), chronic lymphocytic leukaemia (CLL, n = 1, 594), marginal zone lymphoma (MZL, n = 957), follicular lymphoma (FL, n = 725) and classical Hodgkin lymphoma (CHL, n = 255), together with monoclonal gammopathy of uncertain significance (MGUS, n = 2, 138) and monoclonal B‐cell lymphocytosis (MBL, n = 632). Odds ratios (OR) and 95% confidence intervals (95%CI) were calculated relative to 10 age‐ and sex‐matched controls using conditional logistic regression. Having had a joint replacement before diagnosis was associated with myeloma (OR = 1.3, 95% CI 1.1–1.5, p = 0.008) and MGUS (OR = 1.3, 95% CI 1.1–1.5, p < 0.001). Excluding replacements in the year before diagnosis, the MGUS risk remained, elevated where two or more joints were replaced (OR = 1.5, 95% CI 1.2–2.0, p = 0.001), with hip (OR = 1.2, 95% CI 1.0–1.5, p = 0.06) or knee replacements (OR = 1.5, 95% CI 1.2–1.8, p < 0.001). Associations with CHL and two or more replacements (OR = 2.7, 95% CI 1.3–5.6, p = 0.005) or hip replacements (OR = 1.9, 95% CI 1.0–3.4, p = 0.04); and between DLBCL and knee replacements (OR = 1.3, 95% CI 1.0–1.6, p = 0.04) were also observed. Our study reports for the first time a relationship between joint replacements and MGUS; while absolute risks of disease are low and not of major public health concern, these findings warrant further investigation. Abstract : What's new? While lymphoid malignancies are increased in persons with previous joint replacements, data on associations with particular diagnostic subtypes is lacking. Here, the authors investigated the relationship between joint replacement and mature B‐cell neoplasms and their precursor conditions in an established cohort of patients with hematological malignancies linked to national healthcare records. Previous joint replacement was associated with subsequent elevated risk of myeloma, monoclonal gammopathy of uncertain significance, and Hodgkin lymphoma subtypes of hematological disease. While the findings indicate that absolute risks are low, joint replacement procedures are increasing and disentangling the underlying reasons behind these associations warrants further investigation.